Specification faced with durability to meet superior level of performance in structural elements buried - Bolina,F. (2016)
ABSTRACT The performance standard NBR 15575-1: 2013 [1] states that to achieve the higher level of performance for durability, buried concrete structures must achieve a minimum service life (VUP) of 75 years. However, the NBR 6118:2014 [2] does not specify the minimum project properties for the structure fulfill this VUP. The objective of this study is to provide recommendations for structural designers to meet higher performance requirements of NBR 15575:2013 [1] in durability. It was conducted a research of national and international standards and reference publications about the durability and VUP 75 years for structural elements buried. The paper was divided into three parts: (1°) the analysis of the Brazilian and international legal system, as well as reference publications in the area; (2°) discussion of service life prediction models; and (3°) specifications to meet the superior level of durability of structural elements buried.